Woman and the Masjid between Two Extremes (American Journal of Islam and Society, 2006)
The masjid, better known in North America as the Islamic center, is the centerof spiritual, social, educational, and, most recently, political activities ofthe American Muslim community. The masjid is also the place whereMuslims of diverse cultural and ideological backgrounds meet and interact.The diversity of interpretations of Islamic sources and practices has createdtensions, particularly in Islamic centers where the tendency is to imposestrict interpretations about the appropriate place and role of Muslim womenin the masjid and the community.An increasing number of young Muslim women complain of restrictivearrangements and practices, impeding their ability to fully participate in educationaland social programs. Many masjids today restrict the main prayerhall to men and assign women to secluded quarters. Women are asking outloud: “Is this the place Islam assigns for us, or is it the imposition of culturaltraditions?” Some have even gone to the other extreme of rejecting all traditionsand discarding all limits ...